Kampanye Membangun Women Empowerment pada Akun Instagram - Anisa Dwi Nanda Septiningrum; Atie Rachmiatie (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. Magdalene or magdalene.co is one of the pioneering women's online media that focuses on providing content with a critical perspective, empowering, educating, and entertaining related to issues of gender equality and feminism in Indonesia. With a research that entitled